Mount Sinai expert guides. Obstetrics and gynecology - Sperling, Rhoda (Hoboken, NJ : Wiley-Blackwell, 2020)
"Mount Sinai Expert Guides: Obstetrics and Gynecology will provide specialty trainees and junior physicians with an extremely clinical, affordable and accessible handbook covering the key and hot topics in this complex field with focus throughout on clinical diagnosis and effective patient management. Used as a point-of-care resource in the hospital and clinical setting, it will present the very best in expert information in an attractive, quick and easy to navigate informative and well-structured manner, with features such as key points, potential pitfalls, management algorithms, and national/international guidelines on treatment"--
Multiple gestations -- Preeclampsia/eclampsia -- Gestational diabetes -- Viral infections and pregnancy -- Placenta previa and morbidly adherent placenta -- Gastrointestinal disorders and pregnancy -- Ultrasound in pregnancy -- Carrier screening and aneuploidy screening -- Preterm birth -- Abnormal labor -- Cesarean delivery and operative vaginal delivery -- Intrapartum and postpartum hemorrhage -- Intraamniotic infection -- Liver disease and pregnancy -- Thyroid disease and pregnancy -- Perinatal mood and anxiety disorders -- Surgical site infections -- Vaginitis, cervicitis, and pelvic inflammatory disease -- Abnormal uterine bleeding -- Fibroids -- Pelvic organ prolapse -- Stress incontinence -- Adnexal mass -- Endometriosis -- Anogenital HPV -- Genitourinary syndrome of menopause -- Menopausal hot flashes -- Urinary tract infection -- Ectopic pregnancy -- Osteoporosis -- Genital ulcer disease -- Vulvodynia -- Evaluation of the infertile couple -- Ovulation induction/ART/IVF/ICSI -- Polycystic ovary syndrome -- Recurrent pregnancy loss -- Fertility preservation -- Ovarian cancer -- Cervical cancer -- Endometrial cancer -- Gestational trophoblastic disease -- Vulvar cancer -- Unintended pregnancy -- Pregnancy prevention -- Early pregnancy failure
BIBINDX
Keywords: Obstetrics -- Handbooks, manuals, etc; Gynecology -- Handbooks, manuals, etc; Obstetrics; Gynecology; Electronic books; Handbook; Handbooks and manuals; Handbooks and manuals